Regulation Theory and Transformation of Agriculture: a Literature Review - Jean-Marc Touzard and Pierre Labarthe (Revue de la Régulation)
The article is based on a literature review of research related to the French Regulation Theory (RT) and applied to agriculture and food. It analyzes the changes in this sector and proposes a new research agenda. In the first part we examine research findings embedded in RT in the 1980’s and 1990’s, focusing on the emergence and crisis of the economic regime of agriculture of industrialised countries during the fordist period. In the second part we show how this body of research continues the analysis of different dimensions of agricultural transformation, and progressively combines with other research programs. However, we argue that the new international context of agriculture and food is an opportunity to renew RT research on this sector and to understand its different economic regimes and their transitions in various national contexts.